Is the Species Flock Concept Operational? The Antarctic Shelf Case - Ropert-Coudert, Yan; Lecointre, Guillaume; Améziane, Nadia; Boisselier, Marie-Catherine; Bonillo, Céline; Busson, Frédéric; Causse, Romain; Chenuil, Anne; Couloux, Arnaud; Coutanceau, Jean-Pierre; Cruaud, Corinne; d'Acoz, Cédric d'Udekem; et al. (PLoS ONE, 2013)
There has been a significant body of literature on species flock definition but not so much about practical means to appraise them. We here apply the five criteria of Eastman and McCune for detecting species flocks in four taxonomic components of the benthic fauna of the Antarctic shelf: teleost fishes, crinoids (feather stars), echinoids (sea urchins) and crustacean arthropods. Practical limitations led us to prioritize the three historical criteria (endemicity, monophyly, species richness) over the two ecological ones (ecological diversity and habitat dominance). We propose a new protocol which includes an iterative fine-tuning of the monophyly and endemicity criteria in order to discover unsuspected flocks. As a result nine "full" species flocks (fulfilling the five criteria) are briefly described. Eight other flocks fit the three historical criteria but need to be further investigated from the ecological point of view (here called "core flocks"). The approach also shows that some candidate taxonomic components are no species flocks at all. The present study contradicts the paradigm that marine species flocks are rare. The hypothesis according to which the Antarctic shelf acts as a species flocks generator is supported, and the approach indicates paths for further ecological studies and may serve as a starting point to investigate the processes leading to flock-like patterning of biodiversity.